Europe in World Natural Gas Market: International Transmission of European Price Shocks - Kopytin, Ivan Aleksandrovich; Maslennikov, Alexander Oskarovich; Zhukov, Stanislav Vyacheslavovich (International Journal of Energy Economics and Policy, 2022)
The paper applies the Vector Error Correction Model (VECM) framework with 250 days rolling window to the analysis of the interconnectedness of regional markets for natural gas in Europe, the Asia-Pacific region and the US. Transmission of European gas market fundamentals to other regional gas markets is assessed by using carbon price in the EU Emissions Trading System and European gas storage capacity utilization. The latter is proven to be a significant component in the cointegrating equation that links natural gas prices in Europe and the Asia-Pacific region. It is shown that gas prices in all three regional markets are pairwise cointegrated while cointegration between gas and oil prices is absent in Europe and the Asia-Pacific region and weak in the US. It is also concluded that fundamental factors of the European gas market influence gas price dynamics not only in Europe, but also in the Asia-Pacific region and, to a lesser extent, the US. In sum, the increasing importance of LNG import in European natural gas consumption has given a strong impetus to the formation of the global natural gas market.